2017
DOI: 10.1186/s12931-017-0618-6
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus alters lung pathology and viral load following influenza A virus infection

Abstract: BackgroundInhibitors of mTOR, such as sirolimus, have been shown to induce thymus involution and inflammatory lung disease in mice. The latter effect supports the role of this serine/threonine kinase in ameliorating lung inflammation. Other studies have shown sirolimus reduces/delays lung disease associated with various strains of influenza A virus (IAV). Thus, the effects of mTOR inhibitors on influenza infection deserve further studies.MethodsHere, we examined the changes in lung viral copies, pathology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Mice treated with sirolimus had more body weight loss during the illness, and a higher viral load on Day 10 than controls that did not receive sirolimus. However, there was a trend, suggesting lower lung inflammation score as seen in histology specimens (mean score 9.0 ± 4.5 vs 11.5 ± 4.5, p = .335), and improved compliance on mechanical ventilation in the mice that received sirolimus, consistent with drug-promoting apoptosis that lowered experimental lung injury associated with influenza infection ( Alsuwaidi et al, 2017 ).…”
Section: Therapies With Clinical Evidence Of Improved Patient Outcomementioning
confidence: 89%
“…Mice treated with sirolimus had more body weight loss during the illness, and a higher viral load on Day 10 than controls that did not receive sirolimus. However, there was a trend, suggesting lower lung inflammation score as seen in histology specimens (mean score 9.0 ± 4.5 vs 11.5 ± 4.5, p = .335), and improved compliance on mechanical ventilation in the mice that received sirolimus, consistent with drug-promoting apoptosis that lowered experimental lung injury associated with influenza infection ( Alsuwaidi et al, 2017 ).…”
Section: Therapies With Clinical Evidence Of Improved Patient Outcomementioning
confidence: 89%
“…11 Some studies have shown that everolimus, another mTOR inhibitor, and sirolimus are weakly active against influenza A virus. 19,20 Everolimus delayed death but was not able to reduce mortality in lethal mouse infection model of influenza A (H1N1 and H5N1). 19 Sirolimus was even shown to negatively affect the lung pathology probably due to its immunosuppressive effect.…”
Section: Discussionmentioning
confidence: 99%
“…19 Sirolimus was even shown to negatively affect the lung pathology probably due to its immunosuppressive effect. 20 It has also been reported to block viral protein expression and virion release, improving the prognosis in patients with severe H1N1 pneumonia and acute respiratory failure. 21 On the other hand, rapamycin treatment was shown to degrade antiviral barriers and could thus be potentially harmful in pathogenic viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Serial images were stitched into a highresolution macroscopic montage. Tissues were evaluated blindly using an inflammatory histopathologic score (HPS) system that assigns values of 0 to 26 (least to most severe) based on assessment of quantity and quality of peribronchial inflammatory infiltrates, luminal exudates, perivascular and parenchymal infiltrates and thickening of the membrane wall, as described previously (36,37). This scoring system has been previously validated in other mouse models of respiratory infections (37,38).…”
Section: Lung Histopathologymentioning
confidence: 99%